Biogeography of the areas and Canthonini (Coleoptera: Scarabaeidae) of dry tropical forest in Meseoamerica and Colombia - Padilla-Gil, Dora Nancy; Halffter, Gonzalo (Instituto de Ecología, A.C., 2007)
This biogeographical analysis examines the historical, geological, climatic and ecological processes that have influenced the formation of the dry tropical forests (DTF) of Mesoamerica and Colombia, areas that are the setting for multiple biogeographical stories that in this case are illustrated by the patterns and evolutionary processes of Canthonini. In this study we test the hypothesis that the Canthonini fauna of dry tropical forests has a South American affinity. To this end, we compare extant species from a tract of dry tropical forest in Mexico, a second enclave in Costa Rica, four from the Caribbean region of Colombia and finally one from the north of Tolima in the Upper Magdalena River Valley, Colombia. The geomorphological characteristics of the enclaves of DTF are also compared, as are the geographical distribution and taxonomic affinities of each of the species found in these dry tropical forests. The biogeographical, historical and geological aspects of the enclaves were evaluated using a Parsimony Analysis of Endemicity (PAE), with two tropical rain forests as the outgroup: Leticia (Amazonas, Colombia) and Los Tuxtlas (Veracruz, Mexico).This study reveals the origin and distribution of Neotropical dry forests in the Pleistocene, and the establishment of its dry conditions during the Holocene. It also reveals apparent similarities among the Canthonini of the dry tropical forests of Mexico, Costa Rica and Colombia, with three geographical distribution patterns that correspond to different degrees of expansion towards the north and the diversification of evolutionary lines, and even species of South American origin.The comparison of the cladogram generated for species of Canthonini with that of the geological events that have occurred in the study regions indicates that the distribution of Canthonini in dry tropical forests began during the Pliocene with the re-establishment of the Panamanian connection, with no evidence of previous geomorphological events having any influence. On the other hand, there are few species shared with the tropical rain forests used as the outgroup for the cladograms.